OUTCOMES OF REFORMS IN INDIA’S POWER SECTOR: PROGRESS AND CHALLENGES - Sonia; Kumar, Rajesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The power sector can be pivotal in India’s economic growth and development. India has been implementing the electricity sector reform since 1991, aimed at improving efficiency, promoting renewable energy sources, improving distribution, increasing generation capacity, fostering private sector participation, and ensuring reliable electricity supply for economic growth. The outcomes of India's electricity sector reforms are summarised in this study, highlighting the progress and challenges faced during the implementation process. Implementing reforms in the electricity sector in India has yielded significant improvement from 1997-98 to 2021-22. One of the notable achievements has been the increase in installed generation capacity, which has helped bridge the gap between demand and supply of electricity. This has improved operational performance, reduced losses, and improved the financial viability of power utilities. Despite these positive outcomes, India’s power sector faces several challenges. The study explores the specific challenges that the Indian electricity sector faces and provides suggestions for how to resolve them to enhance the sector's sustainability and performance.